The Efforts to prevent the conversion of wetland by management under one institution in Catchment Area Rawapening, Semarang Regency: - Harahap, Tondi (CV. Era Digital Nusantara, 2024)
This paper shows the problems occur in Indonesia urban area to manage their wetland. Having exceptionally large area wetland (thirty-seven million hectares) i.e.: Coastal area, peatland, swamp, lake, river, inside, and riparian that are publicly domain makes conflicts of wetland ecosystem management in Indonesia. Conversion of wetland into urbanize area is one of the problems wetland ecosystem managements. This research aims to investigate the conflicts of interest amongst different stakeholder including private sector, local community, and government. for wetland area especially a case in Rawapening Lake, Semarang. The results are people driven by economic and cultural factor, private sector driven by profit, while government manage wetland area without measuring the impact to environment. For this result, the major conclusion to manage conflict of wetland ecosystem management in urban area is by playing role of the government to point wetland as conservation area and point wetland management state owned enterprises as the authority management.